General Characteristics of Internal Medicine Consultations in the Emergency Service of a University Hospital - Aygencel, Gülbin; Nas, Ahmet; Sarıtaş, Hazen; Deryal, Kerem; Demircan, Ahmet (Fırat University, 2012)
Objective: The purpose of this study was to determine general characteristics of patients who presented to emergency service (ES) of our hospital (OH) and required internal medicine (IM) consultations. Materials and Methods: We evaluated patients aged 18 years and older, who presented to the ES of between Nov 01,2010 and Dec 31,2010 and who were referred for IM consultations. Results: A total of 7100 patients were admitted to ES of during this study period and 546(7,7%) patients were referred for IM consultation. The mean age of the study patients was 60,13±18,10(62; 18-97) and 54,4%(297) of the patients were female. Among the most common causes for the study patients, to present to ES were symptoms related to the gastrointestinal system (31,3%-171) such as abdominal pain, nausea-vomiting, hematemesis or hematochezia and the most frequently observed consultation was IM consultation depending on nephrological causes (34,2%-187) such as high BUN and creatinine levels, and electrolyte imbalance. In addition to the routine examinations such as blood count, biochemical tests, electrocardiography, P-A Chest graphy, urinalysis, 444 patients(81,3%) were referred for further examinations involving either blood or screening methods. In conclusion, 50,4% of the patients were discharged, 4,6% died in the ES and 45% were hospitalized. Conclusion: Determining patient profiles in ES, for whom IM consultations were requested, will contribute to the curriculum of the relevant training programs aiming to train staff in this particular field of medicine and thereby increase the quality of health care services.

Amaç: Hastanemiz acil servisine başvuran ve iç hastalıkları konsultasyonu istenen hastaların genel özelliklerinin belirlenmesidir. Gereç ve Yöntem: 01.11.2010 -31.12.2010 tarihleri arasında hastanemiz acil servisine başvuran ve iç hastalıkları konsultasyonu istenen 18 yaş ve üstü hastalar değerlendirilmeye alınmıştır. Bulgular: Bu 2 aylık süreçte hastanemiz acil servisine toplam 7100 hasta başvurmuş ve 546 (%7,7) hastadan iç hastalıkları konsultasyonu istenmiştir. Konsultasyon istenen hastaların yaş ortalaması 60,13±18,10 (62; 18-97) yıldır ve %54,4'ü (297) kadındır. Konsultasyon istenen hastaların en sık acile başvuru sebebi karın ağrısı, bulantı-kusma, kanlı kusma veya kanlı ishal gibi gastrointestinal sisteme ait semptomlar (%31,3-171) iken; en sık BUN, kreatinin yüksekliği, elektrolit dengesizliği gibi nefrolojik sebeplerle (%34,2-187) iç hastalıkları konsultasyonu istenmiştir. Kan sayımı, biyokimya, elektrokardiyografi, P-A Akciğer grafisi, idrar tetkiki gibi rutin tetkiklerin yanında 444 hastaya (%81,3) kan veya görüntüleme yöntemi olarak ek tetkikler istenmiştir. Sonuçta hastaların %50,4'ü taburcu olmuş, %4,6'sı acilde ölmüş ve %45'i ise hastaneye yatmıştır. Sonuç: Acil servislerde iç hastalıkları konsultasyonu istenen hastaların profillerinin belirlenmesi, bu uzmanlık dalında eleman yetiştiren kurumlarda eğitim programlarının şekillenmesinde ve sağlık hizmet kalitesinin artırılmasında faydalı olacaktır.
Bir Üniversite Hastanesi Acil Servisindeki İç Hastalıkları Konsultasyonlarının Genel Özellikleri